Levantamento populacional de inimigos naturais na cultura da manga (Mangifera indica L.) - De Oliveira, Gustavo F. [UNESP]; Duarte, Rogério T. [UNESP]; Pazini, Wilson C. [UNESP]; Galli, Júlio C. [UNESP] (Revista Brasileira de Ciencias Agrarias, 2013)
The objective of this research was to evaluate the interrelation between populations of natural enemies present in tree canopy, correlated with meteorological elements, and terrestrial biological control agents in a mango grove located in Jaboticabal, SP. The natural enemies related to the tree canopy were monitored with five yellow sticky traps, maintained for 15 days in field and immediately replaced by new traps. To obtain faunistic analyzes we calculated dominance, abundance, frequency and constancy indices. To analyze the tree canopy populations with meteorological elements we calculated the simple linear correlation coefficients (r). The monitoring of natural enemies presents in soil surface was performed with five Pitfall traps, also collected fortnightly, and the data analyzed in histogram. The coccinellid predator Scymnus spp. presents superdominant population. Meteorological elements interfere in occurrence and distribution of natural enemies present in tree canopy of the experimental area. Natural enemies of Formicidae, Staphylinidae, Forficulidae and Carabidae families are the most commonly found in mango grove soil.
Survey population of natural enemies in mango culture (Mangifera indica L.)
Keywords: Biological control; Faunistic indices; Integrated pest management; Meteorological elements; Population fluctuation